Design of Low Voltage Low Power Analog Circuits Based On Quasi-Floating Gate MOSFETs - Kiran, Bhanu (My University, 2016)
The low voltage/ low power techniques are used as an integral part of the design process for any modern electronic device. This requires an extensive research of such techniques to come up with efficient methods to achieve downscaled supply voltage and a resultant low power operation effectively. Quasi-floating gate MOSFET (QFGMOS) is an emerging technique for low voltage/ low power operation. With the advantages offered by it, it has presented itself as a promising substitute of conventional low voltage/ low power techniques. The thesis presents the concept of Quasi-floating gate MOSFET (QFGMOS). The research work includes designing of different analog circuits such as QFGMOS based current-to-voltage converter, current divider and a pseudo-exponential function generator. All the proposed circuits have been simulated using Cadence Virtuoso analog design environment in 180nm CMOS technology. The proposed circuits are operated at the supply voltages of ±0.5V. The simulation results have also been presented to demonstrate the low voltage low power functionality offered by the QFGMOS technique and the other advantages offered by it that make it a promising technology for the future.
M. Tech (VLSI Design)
Keywords: Low Voltage; Low Power; Quasi-Floating Gate MOSFETS